A Novel Classification of Supply Chain Risks: A Review - Shahbaz, M. S.; Sohu, S.; Khaskhelly, F. Z.; Bano, A.; Soomro, M. A. (Engineering, Technology & Applied Science Research, 2019)
Every organization is a complex supply chain system. If any fragment of this supply chain is disturbed, it will directly affect the entire structure. Numerous studies have been conducted to categorize the supply chain risk sources, but very few available cover all types of risks. This study did an extensive literature review and content analysis on the subject. A supply chain is the flow of information, material, and money starting from suppliers and ending to end-users. To cover all types of risks, risk sources must be based on three perspectives: (i) internal to the firm, (ii) external to the firm but internal to the supply chain, and (iii) external to the supply chain. Risks can be categorized into seven types under these three perspectives. Regarding internal risks, three types of risks come from the supply side, process side, and demand side, while these members of the supply chain are connected with the supply affected by logistic side risks, finance side risks, and collaboration side risks. The external environment also affects the supply chain so the seventh type of risks comes from environmental side risks. This study extends the literature of supply chain risk management by identifying new risk sources. This study will help the managers to understand what kind of risks can affect their supply chain. Future study can be conducted to empirically verify these risks sources.